Penerapan the four discipline of execution (4dx) terhadap segitiga manajemen proyek untuk meningkatkan keuntungan proyek - Suhendar, Dadan; Sulistiyadi, Kohar; Hardiyanto, Toto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Various ways and strategies are used by companies to optimize employee performance, one of which is by implementing The 4 Disciplines of Execution. This study aims to obtain an overview of the application of The 4 Disciplines of Execution to improve discipline and create an execution culture so as to improve performance. conducted interview sessions and data collection by filling out questionnaires for all employees of PT Tricon Mitra Utama, a total of 35 respondents, and then added respondents from other companies that implemented The 4 Disciplines of Execution in their companies so that a total of 114 respondents were collected. From the results of statistical analysis with structural model equations with the help of LISREL software, it was found that the application of The 4 Disciplines of Execution has a significant impact on improving performance; this affects the turnaround time to be on time and maintaining good quality work results, but increases the cost of carrying out the work. Based on the balance of time, cost and quality do not have an increasing impact on project profits, but with the completion of work on time and meeting quality standards, the company does not experience cost overruns due to delays and repair work (rework), so that the allocation of costs for the cost of quality, interest, and finality can be absorbed as company profits.